Why Asplenic Patients Should Not Take Care of the Neighbour’s Dog? A Fatal Course of Capnocytophaga canimorsus Sepsis - Patrick Langguth; Lothar Leissner; Günther Zick; Arno Fischer; Christiane Stuhlmann-Laiesz; Mona Salehi Ravesh; Friederike Austein; Olav Jansen; Marcus Both (Case Reports in Infectious Diseases)
Capnocytophaga canimorsus (CC) belongs to the family Flavobacteriaceae which physiologically occurs in the natural flora of the oral mucosa of dogs and cats. In patients with a compromised immune system, CC can induce a systemic infection with a fulminant course of disease. Infections with CC are rare, and the diagnosis is often complicated and prolonged. We describe a patient with a medical history of prior splenectomy who presented with an acute sepsis and disseminated intravascular coagulation (DIC) and was initially treated on Waterhouse–Friderichsen syndrome (WFS). After the patient had died despite forced treatment in the intermediate care unit, the differential diagnosis of CC was confirmed by culture of blood smears. Later on, a retrospective third-party anamnesis revealed that the patient had contact to his neighbour’s dog a few days before disease onset. In conclusion, patients with CC infection can mimic WFS and therefore must be included in the differential diagnosis, especially in patients with a corresponding medical history of dog or cat bites, scratches, licks, or simple exposure.